Taxonomy and Ecology of Mothronwala Swamp, a Reassessment - Deva, Som (Indian Forester, 1974)
1. Swamp in the Dehra Dun Valley have come up as result of special topography where water oozes out in perennial streams. 2. Original forest of Mothronwala has been completely replaced by Pyrus pashia, Lantana camara, Xylosma longifolia scrubs in all the three vegetational zones. Remnant of old forests are present as stumps. 3. Succession on a limited scale of primary herbaceous and bush-fem stage is still perceptible. 4. A provisional scheme leading to the development of swamp forest through Bischofia javanica as a pioneer tree community is provided.